Ultrasonographic Evaluation of Gastric Contents in Term Pregnant Women Fasted for 6 Hours. Issue 1 (March 2019) - Hakak, S.; McCaul, C.L.; Crowley, L.
Abstract : ( Int J Obstet Anesth . 2018;34:15–20) Fasting before elective anesthesia is intended to reduce gastric fluid volume and the risk of aspiration of gastric contents leading to aspiration pneumonitis, which can be life-threatening. Pregnant women are considered to be at increased risk of pulmonary aspiration due to some of the physiological changes of pregnancy, including relaxation of the lower esophageal sphincter and the upward displacement of the stomach by the gravid uterus. Current fasting guidelines vary among national anesthesiology organizations with most recommending at least 6 hours of fasting after a light meal and some suggesting 6 to 8 hours of fasting depending on the type of food consumed before anesthesia for elective procedures. This current prospective study was undertaken to analyze the stomach contents of nonlaboring term pregnant women after 6 hours of fasting, using ultrasonographic assessments.